Migrating motor complex of the intestine and absorption of a biliary excreted drug in the dog - Priymenko, N; Ferre, J P; Rascol, A; Costes, G; Toutain, P L (The Journal of pharmacology and experimental therapeutics, 1993)
The role of the migrating motor complex (MMC) of the small intestine in the absorption of an enterally administered marker (tolfenamic acid, TA) used to investigate enterohepatic recycling was studied in the fasted dog. TA was rapidly and extensively absorbed in the duodenum as well as in the ileum. In contrast, the conjugated form of TA (CTA) was not absorbed in the duodenum but only in the ileum, i.e., after bacterial hydrolysis. By administering CTA in the duodenum at different phases (I and II) of the MMC, it was shown that CTA had to be propelled from the duodenum to the ileum by the motor activity of the MMC. Under these conditions, the peak plasma TA concentration was only observed when phase II of the MMC present in the duodenum at the time of CTA administration arrived in the ileum. The estimated mean transit time of CTA from the duodenum to ileum was 45 min and the mean hydrolysis time of CTA to TA was about 75 min. It was concluded that 1) in the fasted dog, a relatively long delay must exist between bile excretion of a conjugate and the reabsorption of its free moiety in the ileum and 2) a realistic physiological model of enterohepatic recycling must take into account the MMC pattern of the intestine when drugs are administered to animals in the fasted state.